DAYLIGHT OPTIMIZATION IN A CAFÉ THROUGH WINDOW TO WALL RATIO AND ILLUMINANCE ANALYSIS: A CASE STUDY OF BREW AND CHEW CAFÉ IN BANDUNG, INDONESIA - Ardyanny, Yuninda Mukty (architecture department, Engineering faculty, Universitas Diponegoro, 2023)
Daylighting is essential for enhancing the lighting ambiance and ensuring occupants' visual comfort in a café. Nowadays, a café is not only a leisure destination, but also becomes a preferred place for people working remotely. Consequently, the necessity for proper daylighting in a café becomes crucial to achieve customers' visual comfort. Regarding daylighting, windows play a pivotal role in bringing natural light into a building. Thus, the Window-to-Wall Ratio (WWR) percentage has a significant impact on the illuminance level within the building. To prevent visual discomfort, the Leadership in Energy and Environmental Design (LEED) v4.1 Standard for daylight measurement will serve as the parameter to achieve an acceptable level of illuminance, ranging between 300 lux and 3,000 lux at both 9 AM and 3 PM. The objective of this research is to determine the optimal WWR percentage in a case study café to achieve an acceptable illuminance level based on the LEED v4.1 standard, using Velux as the simulation software. The research methodology involves measuring the existing illuminance level of the case study café using a lux meter to validate the building simulation results. Subsequently, the 3D model of the café will be simulated in Velux with varying Window-to-Wall Ratios (WWR) to identify the optimal WWR that aligns with the LEED v4.1 standard for daylight measurement.